Workplace Training: How Context Impacts on Instructors’ Activities - Ouellet, Sylvie (Relations industrielles / Industrial Relations, 2012)
In the present-day world of work, characterized by the globalization of markets and rapid technological change, company directors are turning toward new types of work organization and product diversification in order to contend with increasingly fierce competition. In such a context, workplace training has become a critical issue for companies. Though there are different types of workplace training, the instructors are usually experienced employees who have been asked to train new employees. Incorporating training into the company’s production activities is complex because it creates a situation where the training activity comes into contact with all the other activities. The present article reports on ergonomic research intervention conducted in the meat processing sector which sheds light on the difficulties and challenges that structured training in an SME production system poses for instructors. The data collected here showed that worker-instructors were poorly prepared to train new workers and that the role of an instructor was not sufficiently appreciated in the company. Furthermore, our study pointed out that, to organize learning situations, instructors had to consider several conditions (organizational, technical, physical, and social) and make compromises between what they would have liked to do and what the conditions allowed them to do. Avenues for improvement are suggested to help create greater recognition of the instructors’ role and provide them with more support in the implementation of training activities. The observations made in this study can serve as food for thought for anyone interested in workplace training conditions.